KEBIJAKAN PEMERINTAH DAERAH DALAM PEMBANGUNAN SARANA DAN PRASARANA PENDIDIKAN DI KABUPATEN JAYAWIJAYA PROPINSI PAPUAKEBIJAKAN PEMERINTAH DAERAH DALAM PEMBANGUNAN SARANA DAN PRASARANA PENDIDIKAN DI KABUPATEN JAYAWIJAYA PROPINSI PAPUA - WORABAY, MENASER GASPER (JURNAL ADMINISTRASI PUBLIK, 2018)
Abstract: the purpose of this study is to contribute to the development of science in the field of state administration studies, especially for studies related to local government policy in the development of educational facilities and infrastructure as well as a material information and input for local governmentJayawijaya Regency in improving the quality of education facilities and infrastructure development.the research informants were the Bupati, the Bupati's deputy, the DPRD (Chairman of Commission C), the Head of the Education Office, the Head of Education and Education Facility, and 6 principals, totaling 11 people. Data collection is done by observation, interview and literature study. while data analysis using qualitative analysis technique of interactive model according to Miles and Huberman. based on the results of data analysis concluded that the Local Government as a drafter and implementer of Regional Policy in the development of educational facilities and infrastructure in Jayawijaya Regency in the authority required to improve the quality of education. concerning education facilities and infrastructures in Jayawijaya Regency still need funding and expense big enough to reach adequate standard of education service especially school children of elementary, junior high, and vocational high school. is very important educational facilities and infrastructure and also added with other components such as educational support facilities and educators in supporting the teaching and learning process to maximize the quality of education in Jayawijaya Regency. the increasing quality of education services, especially schools, is strongly influenced by the Visionary Principal's care and commitment, the quality management used and the education / school organizers to provide good education / schools. Keywords: Local Government Policy, Education Facility and Infrastructure.